1255Associations between select lifestyle behaviours and quality of life based on MS phenotype. (2nd September 2021) - Nag, Nupur; Yu, Maggie; Simpson-Yap, Steve; Neate, Sandra; Schmidt, Hollie
Abstract: Background: Multiple sclerosis (MS) comprises progressive and non-progressive phenotypes, both presenting with symptoms that may reduce quality of life (QoL). Lifestyle behaviours, including diet, exercise, and wellness activities, are associated with higher QoL, however little is known about differences by MS phenotype. We assessed associations between lifestyle behaviours and QoL, between progressive vs non-progressive MS. Methods: Self-reported cross-sectional data from the iConquerMS study (n = 1, 109) were analysed. Lifestyle behaviours were queried via tick-box options for diet-type, supplement use, and wellness activities; and physical activity via Godin-Shephard Leisure-Time Physical Activity Questionnaire. QoL was queried via Neuro-QoL. Linear regression, adjusted for age, sex, BMI, education, disability, and MS duration, was used to assess associations and moderation analyses to assess differences between MS phenotypes. Results: Diet-type, physical activity, and wellness activities were associated with specific QoL subdomains. Only associations between diet and physical activity, with QoL subdomains, differed between phenotypes. Anti-inflammatory diets were associated with a 1.5-point increase in mobility in progressive MS. In non-progressive MS, high physical activity was associated with a 3.6-point decrease in depression, and a 4.2-, 2.3- and 3.0-point increase in positive affect, fine motor skills, and social participation, respectively. Conclusions: Specific lifestyle behaviours were associated with QoL subdomains. Associations between diet and physical activity with QoL differed between MS phenotype. Key messages: Specific lifestyle behaviours are associated with higher QoL. Lifestyle interventions for MS management should consider disease course.